Putts that get missed on the right: Investigating lateralized attentional biases and the nature of putting errors in golf - Roberts, R.; Turnbull, O. H. (Journal of Sports Sciences, 2010)
Although the effects of lateral biases in visual attention ("pseudoneglect") have been examined in real-world settings, this phenomenon has yet to be considered within the realm of sporting performance. In the present study, we investigated the effects of pseudoneglect on putting errors in golf. Novice golfers (n = 30) performed 90 putting trials followed by a series of pseudoneglect tasks: requiring participants to bisect lines manually and with a biomechanical bisection tool. All pseudoneglect measures were performed with both the left and right hands. Results demonstrated a leftward bias for all the pseudoneglect tasks, and a rightward bias for putting error. Moreover, the results revealed that individuals who bisected lines to the left on the Bisection Tool (the typical class of pseudoneglect error for humans) with the left hand (the hand that typically produces the greatest pseudoneglect bias) displayed significantly smaller rightward putting errors. Moreover, these individuals also holed more putts. No other pseudoneglect tasks were shown to impact on putting performance. Our findings suggest that lateralized attentional biases have a significant effect on sport performance; they appear to influence a wide range of precision-based sports (e.g. shooting, archery). Findings are also discussed in terms of the processes that are likely to be involved in this effect.